Confidence and Students' Access of Part-Time Labor in Kalimantan Tengah - Lien Meilan; Evi Mariani (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
Based on interviews, this research aims to find out how motivation and factors that encourage students to carry out college activities, namely learning as their responsibility to become students and in addition to that also undergo activities to work. Research was conducted using a qualitative method with a case study approach. Whereby research closely investigates an event, activity, process, or group of individuals. Cases are limited by time and activity, and research collects complete information using various data collection procedures based on a predetermined time. The subjects studied were students who studied while working. From the results of the study, it shows that the reason why students choose to study while working is because of the internal motive where there is a direct impetus related to individual activities, not merely to fulfill basic personal needs but also to improve self-quality and increase self-experience in work, increase high competitiveness as well as to plan future careers.